2019
DOI: 10.1093/molbev/msz167
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Cholesterol Biosynthesis Pathway in Animals

Abstract: Cholesterol plays essential roles in animal development and disease progression. Here, we characterize the evolutionary pattern of the canonical cholesterol biosynthesis pathway (CBP) in the animal kingdom using both genome-wide analyses and functional experiments. CBP genes in the basal metazoans were inherited from their last common eukaryotic ancestor and evolutionarily conserved for cholesterol biosynthesis. The genomes of both the basal metazoans and deuterostomes retain almost the full set of CBP genes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 49 publications
3
50
0
1
Order By: Relevance
“…Cholesterol and its derivatives are essential for all eukaryotes as both a vital structural component of cellular membrane and a precursor to important biomolecules . However, unlike mammals, insects and other arthropods cannot synthesize sterols de novo , and thus typically obtain them from food. Previous studies have demonstrated that interfering with dietary cholesterol usage delays insect growth and increases insect mortality …”
Section: Introductionmentioning
confidence: 99%
“…Cholesterol and its derivatives are essential for all eukaryotes as both a vital structural component of cellular membrane and a precursor to important biomolecules . However, unlike mammals, insects and other arthropods cannot synthesize sterols de novo , and thus typically obtain them from food. Previous studies have demonstrated that interfering with dietary cholesterol usage delays insect growth and increases insect mortality …”
Section: Introductionmentioning
confidence: 99%
“…b Distribution of identified genes in each taxon group. The phylogenetic topology was based on previous studies 97 , 98 . Note that only representative taxa are listed in the tree; for insects, a total of 233 species from 20 orders were investigated (see “Methods”), while all the animal taxa listed in the NR database were subject to screening.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of this family from the cnidarian species studied here implies that these species lack de novo cholesterol synthesis and would need to receive this important signaling molecule from their environment and diet. Studies on the evolution of the cholesterol biosynthesis genes found losses in Cnidaria 58 . This is in line with research that indicated cholesterol as the most prominent sterol (50–63%) in lipid samples of cnidarians as a result of their generally carnivorous diet 59 .…”
Section: Discussionmentioning
confidence: 99%